Model Peningkatan Loyalitas Dosen Melalui Kepuasan Kerja Dosen - Timbul Arifin; Mutamimah Mutamimah; Mutamimah Mutamimah (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2009)
The objective of this study is to examine and analyze the effects of competence, leadership transformation, promotion, motivation to satisfaction and loyalty. To test these variables, this study uses lecturer of Semarang Merchant Marine Polytechnics as a research object, where they are mostly composed of lecturer who have a maritime educational background and work experience as a officer on board ship that joined to the national and international companies indomestic trade area and ocean going trade area with relatively higher income compared to income as an employee or ordinary civil servants. This research was conducted by survey method by distributing questionnaires to 62 people of lecturer who worked and teaches at Semarang Merchant Marine Polytechnics. This study used a non probability sampling with census sampling techniques. The results showed that a competence, leadership transformation, promotion and motivation had positively influence with the satisfaction of lecturer who worked and teaches at Semarang Merchant Marine Polytechnics. Besides teaching competence, leadership transformation, promotion and motivation had positively influence with loyalty of the lecturers who worked and taught at Semarang Merchant Marine Polytechnics through satisfaction variable, as a intervening variable.Keywords: Competence, leadership transformation, promotion, motivation, satisfaction, and loyalty